PENGUATAN NILAI PANCASILA MELALUI KEGIATAN MASA PENGABDIAN SANTRI (MPS) PUTRI DI MA NASY’ATUL MUTA’ALLIMIN GAPURA SUMENEP - Juwairiyah, Ikne (JURNAL SETIA PANCASILA, 2021)
The research was conducted the determine the strengthening of the value of Pancasila throught the activities of the devotion of female students and to find out how the implementation of the value of Pancasila through the activities of the service of students in the MA Nasy’atul Muta’allimin. The population in this study was 67 students and a sample of 20 students was taken. Data collection techniques carried out by observation, interview and documentation. By coming and directly researching the activities of the 22-day period of student devotion. By understanding the situation and the changes that accurred after the activities of the santri devotion period were carried out. The results showed that there was a strengthening of the value of Pancasila which was carried out in the activities of the devotion of the students. The strengthening of the first precepts is strengthened through the activities of istighasah, study akhlaqul libanat, rihlah and madrasah aswaja. The strengthening of the second principle is strengthened through the activities of the study akhlaqul libanat and madrasah aswaja. The strengthened of the third precepts was strengthened through handicraft activities, culinary practices, rihlah and madrasah aswaja. The strengthening of the fourth principle is carried out through handicraft activities, and culinary practices. The strengthening of the fifth precepts is strengthened through the activities of zero plastic movements, handicrafts and culinary practices.